Sorbitol-6-Phosphate Dehydrogenase Expression in Transgenic Tobacco : High Amounts of Sorbitol Lead to Necrotic Lesions - Sheveleva, Elena V. (American Society of Plant Physiologists, 1998)
We analyzed transgenic tobacco (Nicotiana tabacum L.) expressing Stpd1, a cDNA encoding sorbitol-6-phosphate dehydrogenase from apple, under the control of a cauliflower mosaic virus 35S promoter. In 125 independent transformants variable amounts of sorbitol ranging from 0.2 to 130 μmol g(−1) fresh weight were found. Plants that accumulated up to 2 to 3 μmol g(−1) fresh weight sorbitol were phenotypically normal, with successively slower growth as sorbitol amounts increased. Plants accumulating sorbitol at 3 to 5 μmol g(−1) fresh weight occasionally showed regions in which chlorophyll was partially lost, but at higher sorbitol amounts young leaves of all plants lost chlorophyll in irregular spots that developed into necrotic lesions. When sorbitol exceeded 15 to 20 μmol g(−1) fresh weight, plants were infertile, and at even higher sorbitol concentrations the primary regenerants were incapable of forming roots in culture or soil. In mature plants sorbitol amounts varied with age, leaf position, and growth conditions. The appearance of lesions was correlated with high sorbitol, glucose, fructose, and starch, and low myo-inositol. Supplementing myo-inositol in seedlings and young plants prevented lesion formation. Hyperaccumulation of sorbitol, which interferes with inositol biosynthesis, seems to lead to osmotic imbalance, possibly acting as a signal affecting carbohydrate allocation and transport.